Electric vehicle adoption in a mature market: A case study of Norway. (January 2023) - Yang, Anni; Liu, Chenhui; Yang, Di; Lu, Chaoru
Abstract: The transportation sector, led by the automobile, is the major contributor to greenhouse gas emissions and increasing global warming. Transport electrification is one of the effective solutions to reduce oil dependency and mitigate environmental and climatic impacts from road transportation. Norway aims to be a major force in the electric vehicle market and has the ambition to have all newly sold light-weight vehicles be zero-emission by 2025. The share of battery electric vehicles (BEVs) in the auto market in Norway had reached up to 64.5% in 2021, indicating that Norway has recently become a well-matured BEV market. Some previous studies have investigated the drivers of BEV adoption in different countries but primarily in areas with low BEV market share. The drivers of a well-mature market with high BEV adoption remain poorly understood. Additionally, some existing works ignored the impacts of climatic conditions on BEV adoption, although climate conditions have been considered as one of the most important factors that impact BEV performance. In this study, we estimated how socioeconomic drivers and climatic conditions affect the spatial patterns of Norwegian BEV adoption in 2019 using the conditional autoregressive models. We found that the BEV adoption in Norway have a significant clustering pattern. Norwegians in urban areas with more available charging stations and having higher income levels and demand for travel are more likely to adopt BEVs. Municipalities with lower minimum temperatures and a higher proportion of elderly people often have a lower BEV adoption rate. Our findings emphasized the impacts of climatic conditions on BEV adoption and could provide important insights into the late-stage BEV adoption market for many countries in which the current BEV market is still in development.